A importância do acompanhante à gestante em trabalho de parto e parto normal: contribuições a partir de uma revisão integrativa da literatura - CUNHA, Helayni Cristina De Oliveira da (2019)
The purpose of this study was to describe the importance of the presence of the companion, their contributions and the main aspects that make it difficult to enter the parturitive process, according to the scientific publications from 2012 to 2016. The studies were selected from indexed publications In the databases LILACS and BDENF, through the descriptors: Formal companions in Physical Examinations; Pregnancy; Patient’s companion; Labor; Humanized birth. It was decided to include complete articles, in Portuguese and related to the theme, in the period from 2012 to 2016. Based on these criteria, we selected 07 articles, which comprised the analysis and discussion of the final study, with 04 on the base of data LILACS and 03 in the BDENF. From the results it was possible to show that despite the importance and contributions of the companion to the parturitive process, as well as the difficulties of insertion of the same in this context, the collection of scientific productions related to the theme is still sparse. To discuss the importance of the companion figure in the parturition process is of significant importance for the demystification of childbirth and for the process of institutionalizing the humanization of childbirth in the hospital scope.